Unilateral Temporal Lobe Damage and the Partial Kluver–Bucy Syndrome - G. D. L. Bates; S. G. Sturman (Behavioural Neurology)
The characteristic behavioural constellation of Kluver–Bucy syndrome is believed to be diagnostic of bilateral temporal lobe damage, even in the partial syndrome. The case described is that of a 54 year old woman with gross atrophy of her right temporal lobe following neurosurgery who developed hyperphagia (with driven food-seeking behaviour), placidity and hyposexuality. Her case thereby meets criteria for the partial syndrome but without evidence of bilateral damage. The discussion covers the various presentations of hyperphagia, the significance of the symptom cluster of Kluver–Bucy syndrome and the management difficulties presented by hyperphagia.